Primary cutaneous leiomyosarcoma of the flank: Case report and review - J. Ben Hassouna; F. Saadallah; B. Mezghani; M. Ali Ayedi; L. Charfi; L. Achouri; T. Dhieb; K. Rahal (Wolters Kluwer Medknow Publications, 2015)
Cutaneous leiomyosarcoma is a rare soft tissue sarcoma. We present a case of a 50-year-old man, with a rare location in the flank. Clinical presentation showed an ulcerative lesion. Imaging features were evocative of malignancy. Surgical excision was performed, involving oblique muscles. The diagnosis of low-grade leiomyosarcoma with free margins was made. No adjuvant therapy was indicated. Clinical and radiological follow-up of the patient during two years did not reveal recurrences. Cutaneous leiomyosarcoma of the flank is extremely rare and takes part in a group of infrequent and unknown tumors. Clinical presentation is unspecific and histological evidence is mandatory for diagnosis. Tumor extension in depth constitutes the major determinant factor for therapeutic management and prognosis. Wide surgical resection is crucial to minimize recurrence risk especially when poor prognostic factors take place.